In situ preparation of a Bi2O2CO3/BiOI with 2D/2D p-n heterojunction photocatalyst for water purification under visible light - Wu, Xiaoge; Qin, Nan; Yan, Lei; Ji, Renlong; Wu, Di; Hou, Zhenhua; Peng, Weihua; Hou, Jianhua (Frontiers in Chemistry, 2023)
The Bi2O2CO3/BiOI (BOC/BOI) with 2D/2D p-n heterojunction was prepared by one-pot room-temperature strategy. BOC/BOI heterojunction with oxygen vacancies showed much higher photocatalytic activity than pure BOC and BOI. For example, the preferred BOC/BOI-0.5 heterojunction of the degradation rate for Rhodamine B (RhB) is 97.6 % within 2 h, which is 15.8 and 2.2 times faster than that of BiOI and BOC. In addition, the removal rates of tetracycline, ciprofloxacin and bisphenol A by BOC/ BOI-0.5 were 92.4, 80.3 and 68.6%, respectively. The 2D/2D structures of BOC/BOI-0.5 with rich in oxygen vacancies combined p-n junction can effectively inhibit the photoinduced electron-hole pair recombination and increase the production of active free radicals. The •O2- and h+ are the main reactants, giving the composite catalyst potential for degrading a variety of pollutants.